Türkiye'de modernleşme ve propaganda Yeni Cumhuriyet"i tanıtmak, La Turquie Kemaliste Dergisi (1934-1948) - Okumuş, Büşra Türkan (İstanbul Bilgi Üniversitesi, 2017)
[Abstract Not Available]
Modernisation and propaganda in Turkey: introducing the New Republic La Turquie Kemaliste